(untitled) (Journal of Engineering, 2016)
Practically, torsion is normally combined with flexure and shear actions. Even though, the behavior of reinforced concrete continuous beams under pure torsion is investigated in this study. It was performed on four RC continuous beams under pure torsion. In order to produce torsional moment on the external supports, an eccentric load was applied at various distances from the longitudinal axis of the RC beams until failure. Variables considered in this study are absolute vertical displacement of the external supports, torsional moment’s capacity, angle of twist and first cracks occurrences. According to experimental results; when load eccentricity increased from 30cm to 60cm, the absolute vertical displacement increased about 46.92% and the angle of twist increased about 45.76% at failure. It has been also found that the ultimate failure loads decreased about 49.65% when the load eccentricity increased from 30cm to 60cm. Furthermore, the first crack was monitored and it was found that the first crack occurred at higher stages of loading with low loading eccentricity. The first crack records appeared at 75.86%, 70.80%, 63.16% and 54.79% of loading when the load eccentricities are 30, 40, 50 and 60cm, respectively.